Biomarkers of cardiac injury as a prognostic indicator in ARDS - Dina Abdelmonsef Abdelkhalek; Gamal Hamed; Sanaa Abd El Shafee; Yasser Nassar (Cairo : Dina Abdelmonsef Abdelkhalek, 2010)
To evaluate levels of NT pro-BNP, Troponin 1 and troponin T in ARDS patients with structurally normal hearts and to detect the association between these markers with 30 day mortality and other respiratory parameters and scoring systems. Patients and Methods: 20 patients diagnosed to have ARDS according to the criteria of the American-European consensus conference in 1994 admitted from 1 June 2008 until 1 April 2009
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: NT-proBNP; Troponin 1; Troponin T